PENERAPAN MODEL PEMBELAJARAN KOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR SISWA KELAS V DI SDN 188/VIII WIROTO AGUNG KABUPATEN TEBO - Wulandari, Titis; Putra, Randi Eka; Hakiki, Muhammad; apdoludin, apdoludin; R, Hidayati (Information Technology Education Department, 2021)
The problem in this study is the low process and learning outcomes of students in science learning, this is evidenced by the results of observations and school documentation which shows that of 19 students only 47% have met the KKM. This research was conducted in Class V SDN 188/VIII Wiroto Agung. The purpose of this study was to describe and determine the application of the jigsaw cooperative model in increasing the activities and learning outcomes of science in class V. The method used in this study was classroom action research (CAR). This research consists of 2 cycles, each cycle is carried out through 4 stages, namely planning, action, observation and reflection and consists of 2 meetings. The results of the study can be explained as follows: (1) the application of the jigsaw cooperative model in learning activities seen from the observation sheet, namely the first cycle from the teacher aspect 84% and the student aspect 57% while in the second cycle there was an increase in the teacher aspect 91% and the student aspect 73 % who have reached the success indicator. (2) the application of the jigsaw cooperative model in learning in the first cycle is still not optimal. It can be seen from the test results in the first cycle that only 32% of students met the KKM and in the second cycle there was an increase of 79% of students who met the KKM. Thus, it can be concluded that the jigsaw cooperative model can improve the learning process and results at SDN 188 VIII Wiroto Agung.